Pemberian Kombinasi Ekstrak Etanol Daun Pepaya (carica papaya l.) Pada Mencit - rani prabandari (Viva Medika, 2019)
The natural medicine has been known and used through out of the world. One of them is papaya. Efficacy papaya leave provide efficacy as fever, appetite enhancer, launsed menstruation and relieve pain. This study aims to determine whether the effect of aethanol extract of papaya leaf against power analgesic mefenamic acid on mice by using the method asetic acid induction. This study is an experimental study using twenty four mice. This animals were divided into six groups where each group consisting of four mice. Papaya leaves, mefenamic acid, and aquadest were give to each group as test substances and comparative solution. Observations were carried out for 10 minute using the method of asetic acid induction was a decreases of protection mechanism of the mice in of licking or stiff feet responses after the administration of test substances. There was a decrease of the response of mice to lick feet or stiff feet to the asetic acid induction were given after administration of papaya leaf extract. The extract of papaya leaves has an analgesic effect on mice.